Effects of Refrigerated Storage on the Physicochemical, Color and Rheological Properties of Selected Honey - Piepiórka-Stepuk, Joanna; Sterczyńska, Monika; Stachnik, Marta; Pawłowski, Piotr (MDPI AG, 2026)
The paper presents a study of changes in selected physicochemical properties of honeys during their refrigerated storage at 8 +/- 1 degrees C for 24 weeks. On the basis of the study of primary pollen, the botanical identification of the variety of honeys was made-rapeseed, multiflower and buckwheat honey. The samples were stored for 24 weeks in dark, hermetically sealed glass containers in a refrigerated chamber (8 +/- 1 degrees C, 73 +/- 2% relative humidity). The comprehensive suite of analyses comprised sugar profiling (ion chromatography), moisture content determination (refractometry), pH and acidity measurement (titration), electrical conductivity, color assessment in the CIELab system (Delta E and BI indices), texture parameters (penetration testing), rheological properties (rheometry), and microscopic evaluation of crystal morphology; all data were subjected to statistical treatment (ANOVA, Tukey's test, Pearson correlations). The changes in these parameters were examined at 1, 2, 3, 6, 12, and 24 weeks of storage. A slight but significant increase in moisture content was observed (most pronounced in rapeseed honey), while all parameters remained within the prescribed limits and showed no signs of fermentation. The honeys' color became markedly lighter. Already in the first weeks of storage, an increase in the L* value and elevated Delta E indices were recorded. The crystallization process proceeded in two distinct phases-initial nucleation (occurring fastest in rapeseed honey) followed by the formation of crystal agglomerates-which resulted in rising hardness and cohesion up to weeks 6-12, after which these metrics gradually declined; simultaneously, a rheological shift was noted, with viscosity increasing and the flow behavior changing from Newtonian to pseudoplastic, especially in rapeseed honey. Studies show that refrigerated storage accelerates honey crystallization, as lower temperatures promote the formation of glucose crystals. This accelerated crystallization may have practical applications in the production of creamed honey, where controlled crystal formation is essential for achieving a smooth, spreadable texture.